Youth prospects in the digital society identities and inequalities in an unravelling Europe - Bynner, John 1938-; Heinz, Walter R. 1939- (Policy Press, 2021)
This book assesses the challenges young people face in the contemporary labour markets of England and Germany in the context of mass migration, rising nationalism and accelerating technological change, and considers the resources and skills young people in Europe will need in the future
Keywords: Geschichte 1990-2021; Youth / England / Social conditions / 21st century; Youth / Germany / Social conditions / 21st century; Jugend; Soziale Situation; Soziale Ungleichheit; Sozialstruktur; Soziale Identität; Digitalisierung; Deutschland; Großbritannien